2011
DOI: 10.1038/nbt.1929
|View full text |Cite
|
Sign up to set email alerts
|

A resource of vectors and ES cells for targeted deletion of microRNAs in mice

Abstract: The 21-23 nucleotide single-stranded RNAs classified as microRNAs (miRNA) perform fundamental roles in a wide range of cellular and developmental processes. miRNAs regulate protein expression through sequence-specific base pairing with target messenger RNAs (mRNA) reducing both their stability and the process of protein translation1, 2. At least 30% of protein coding genes appear to be conserved targets for miRNAs1. In contrast to the protein coding genes3, 4, no public resource of miRNA mouse mutant alleles e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 40 publications
1
78
0
Order By: Relevance
“…The Six2-Cre-mediated knockout of Dicer1 (Nagalakshmi et al 2011) has already demonstrated the importance of miRNAs in these cells, and specific miRNAs found deregulated in Wilms' tumors would be strong candidates to analyze for their roles in nephron progenitors. A mouse ESC resource for the generation of miRNA reporter and conditional knockout alleles has been described (Prosser et al 2011), and, combined with Cre drivers active in many different cell types in the developing kidney, this would provide the experimental platform to analyze this in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…The Six2-Cre-mediated knockout of Dicer1 (Nagalakshmi et al 2011) has already demonstrated the importance of miRNAs in these cells, and specific miRNAs found deregulated in Wilms' tumors would be strong candidates to analyze for their roles in nephron progenitors. A mouse ESC resource for the generation of miRNA reporter and conditional knockout alleles has been described (Prosser et al 2011), and, combined with Cre drivers active in many different cell types in the developing kidney, this would provide the experimental platform to analyze this in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Previously targeted ES cells at each of the three miR-196 loci have been generated (74). Correctly targeted JM8A3 ES cells were reconfirmed by Southern blot and used to generate germ-line transmitting KO lines.…”
Section: Mir-196a1mentioning
confidence: 99%
“…Recent progress includes resources for miRNA overexpression in Drosophila, which cover 165 miRNAs (Bejarano et al, 2012;Schertel et al, 2012;Szuplewski et al, 2012). Collections of targeted knockout ES cells will facilitate production of miRNA mutant mice (Park et al, 2012;Prosser et al, 2011).…”
Section: Introductionmentioning
confidence: 99%